Analysis of Investment Strategy and Effectiveness of Risk Diversification in Property Investment - Andini, Bunga; Mardiyah, Suci; Sudirman, Wahyu Febri Ramadhan (Journal of Financial and Business, 2025)
Property investment is one of the most popular long-term investment instruments due to its potential to generate stable income and achieve asset value appreciation over time. As a tangible asset, property is often perceived as relatively secure compared to financial assets; however, it is not free from risk. Property investment is exposed to various uncertainties, including market volatility, fluctuations in economic conditions, location-specific risks, regulatory changes, and relatively low liquidity compared to other investment instruments. These risk factors may negatively affect investment performance if not properly managed. Therefore, a comprehensive analysis of property investment risk is essential to support informed investment decision-making. One effective approach to managing investment risk is portfolio diversification, which involves allocating funds across different asset classes to reduce dependence on a single source of return. Diversification aims to minimize unsystematic risk while optimizing the overall risk–return trade-off of the portfolio. Integrating property assets into a diversified investment portfolio can provide benefits such as income stability, inflation hedging, and risk reduction due to low correlation with certain financial assets. This study emphasizes the importance of analyzing the effectiveness of risk diversification in investment portfolios that include property assets.